Prevalence and Factors Associated With Sexually Transmitted Infections Among Women of Reproductive Age in Tanzania: A Cross‐Sectional Analysis of National Data - Fabiola V. Moshi; Jovin R. Tibenderana; Thadei Liganga; Jomo Gimonge; Sanun Ally Kessy (Health Science Reports)
ABSTRACT Background and Aims Sexually Transmitted Infections (STIs) remain a significant public health concern, particularly among women of reproductive age (WRA) who face heightened vulnerability. Despite remarkable advancements in medicine, 1 million new cases of STIs are recorded daily. In Tanzania, however, data on STIs remains limited. This study seeks to bridge that gap by determining prevalence and factors associated with STIs among WRA in Tanzania. Methods This was analytical cross‐sectional study among WRA in Tanzania, using data from the current Demographic and Health Surveys (DHS) 2022. 15,254 weighed sample was analyzed using STATA version 18. Analysis considered the complex survey design through application of weights, clustering and strata. Modified Poisson regression models estimated the factors associated with STIs among WRA in Tanzania. Results were presented using adjusted relative risk (ARR) with a 95% confidence interval. Results The prevalence of STIs among WRA in Tanzania was 4.7%. After adjusting for other variables, the following factors remained significantly associated with STIs among WRA: women aged 25–34 (ARR = 1.55, 95% CI:1.22–1.95), women from rich household (ARR = 1.39, 95% CI: 1.02–1.89), marriage (ARR = 0.81, 95% CI:0.65–0.99) and multiple sexual partners (ARR = 1.80, 95% CI:1.24–2.63). Conclusion Although STIs have a relatively low prevalence (4.7%) among Tanzanian WRA, behavioral change campaigns, young adult‐friendly health services, routine screening and tailored preventive education are crucial to achieving universal health goals, reducing new infections, and fostering the overall well‐being of this vulnerable group.